Triphenyltelluronium Halo (mixed) Titanates(IV) - Verma, K.K.; Saini, Anita; Agrawal, O.P. (Asian Journal of Chemistry, 2010)
The paper reports the synthesis and properties of triphenyltelluronium halo (mixed) titanates (IV)º. 1 : 1. Ph3TeX.TiX´4 and 2 : 1, 2Ph3TeX.TiX´4 (where X,X´═Cl, Br, I) type products are obtained by reactions of Ph3TeX with TiX´4. Conductivity, molecular weight determinations and 1H nmr are consistent with their dissociation in dilute solution as Ph3Te+ and TiX´4X– or Ph3Te+ and TiX´4X22– units. The absence of Te–Ti and Te–X vibrations in the far i.r. spectra of these compounds reflects the transfer of halogen atom from Ph3 TeX to TiX´4 thus resulting in the formation of halo (mixed) titanate (IV) ions.